Evolutionary bedfellows: Reconstructing the ancestral state of autotomy and regeneration. Issue 2 (18th June 2020) - Dunoyer, Luc A.; Seifert, Ashley W.; Van Cleve, Jeremy
Abstract: Some form of regeneration occurs in all lifeforms and extends from single‐cell organisms to humans. The degree to which regenerative ability is distributed across different taxa, however, is harder to ascertain given the potential for phylogenetic constraint or inertia, and adaptive processes to shape this pattern. Here, we examine the phylogenetic history of regeneration in two groups where the trait has been well‐studied: arthropods and reptiles. Because autotomy is often present alongside regeneration in these groups, we performed ancestral state reconstructions for both traits to more precisely assess the timing of their origins and the degree to which these traits coevolve. Using an ancestral trait reconstruction, we find that autotomy and regeneration were present at the base of the arthropod and reptile trees. We also find that when autotomy is lost it does not re‐evolve easily. Lastly, we find that the distribution of regeneration is intimately connected to autotomy with the association being stronger in reptiles than in arthropods. Although these patterns suggest that decoupling autotomy and regeneration at a broad phylogenetic scale may be difficult, the available data provides useful insight into their entanglement. Ultimately, our reconstructions provide the important groundwork to explore how selection may have played a role during the loss of regeneration in specific lineages. Abstract : Ancestral state reconstruction demonstrates that autotomy and regeneration were present in the basal ancestors of arthropods and squamate reptiles. Research Highlights: Ancestral state reconstruction demonstrates that autotomy and regeneration were present in the basal ancestors of arthropods and squamate reptiles and that the distribution of regeneration is intimately connected to autotomy.